PENGARUH PERMAINAN GOBAK SODOR TERHADAP PERKEMBANGAN SOSIAL ANAK DI TK NEGERI 02 PANCUNG SOAL PESISIR SELATAN - Fahira Yupita fahirayupita; Rakimahwati; Serli Marlina; Vivi Anggraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social development is an important aspect that needs to be developed from an early age because it plays a role in shaping children's abilities to interact, cooperate,communicate, and adapt to the social environment. Based on the results ofobservations at TK Negeri 02 Pancung Soal Pesisir Selatan, there are still childrenwho have difficulty in working together, choosing friends, are less able to share, and do not dare to interact actively. This study aims to determine the effect of the gobak sodor game on the social development of children aged 5-6 years at TK Negeri 02 Pancung Soal Pesisir Selatan. The study used a quantitative approach with a quasiexperimental method and a Nonequivalent Control Group Design. The researchsample consisted of 30 children consisting of 15 children in the experimental class and 15 children in the control class. Data collection was carried out through observations using a social development assessment sheet that includes nine indicators. Data were analyzed using normality tests, homogeneity tests, and independent sample t-tests using SPSS version 23. The results showed that theaverage social development score in the control class increased from 18.53 to 21.46 (a difference of 2.93), while in the experimental class it increased from 18.13 to31.33 (a difference of 13.20). The results of the hypothesis test showed a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between the experimental and control classes. Therefore, the game of gobak sodor significantly influences the social development of children aged 5–6 years at TK Negeri 02 Pancung Soal Pesisir Selatan.